Distribution and insertion numbers of transposable elements in species of the Drosophila saltans group - Castro, Juliana P. de [UNESP]; Setta, Nathalia de [UNESP]; Carareto, Claudia Marcia A. [UNESP] (Sociedade Brasileira de Genética, 2006)
Information about the distribution and insertion numbers of many transposable elements is restricted to few species of Drosophila, although these elements are widely distributed throughout the genus. The aim of this work was to describe the distribution and insertion numbers of four retrotransposons (copia, gypsy, micropia, I) and four transposons (hobo, mariner, Minos and Bari-1) in the saltans group of Drosophila. Our data shows that, except for mariner, all the other elements are widespread within the saltans group and show variable insertion numbers of up to 24 copies.
Keywords: Drosophila; genomic insertion; saltans group; Retrotransposon; transposons